Proper motion of the Sextans dwarf galaxy from Subaru Suprime-Cam data - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Schriefer, Michael (Monthly Notices of the Royal Astronomical Society, 2018)
We have measured the absolute proper motion of the Sextans dwarf spheroidal galaxy using Subaru Suprime-Cam images taken at three epochs, with a time baseline of ~10 yr. We astrometrically calibrate each epoch by constructing distortion-correction 'maps' from the best available Subaru Suprime-Cam dithered data sets and from Gaia Data Release 1 positions. The magnitude limit of the proper motion study is V ~ 24. The area covered is 26.7 × 23.3 arcmin2, which is still within the core radius of Sextans. The derived proper motion is (μα, μδ) = (-0.409 ± 0.050, -0.047 ± 0.058) mas yr-1. The direction of motion is perpendicular to the major axis of the galaxy. Our measurement, combined with radial velocity and distance from the literature, implies a low eccentricity orbit, with a moderate inclination to the Galactic plane, and a period of 3 Gyr. Sextans is now some 0.4 Gyr away from its pericentre (rperi ~ 75 kpc), moving towards its apocentre (rapo ~ 132 kpc). Its orbit is inconsistent with membership to the vast polar structure of Galactic satellites. © 2018 The Author(s).
Keywords: Astrometry; Galaxies: dwarf; Galaxies: individual: Sextans; Proper motions; dept.phy; peer-reviewed

A spectroscopic survey of field red horizontal-branch stars - Afşar, Melike; Bozkurt, Zeynep; Topcu, Gamze Böcek; Casetti-Dinescu, Dana I.; Sneden, Christopher; Şehitog̅lu, Gizem (The Astronomical Journal, 2018)
A metallicity, chemical composition, and kinematic survey has been conducted for a sample of 340 candidate field red horizontal-branch (RHB) stars. Spectra with high resolution and high signal-to-noise ratio were gathered with the McDonald Observatory 2.7 m Tull and the Hobby-Eberly Telescope echelle spectrographs, and were used to determine effective temperatures, surface gravities, microturbulent velocities, [Fe/H] metallicities, and abundance ratios [X/Fe] for seven α and Fe-group species. The derived temperatures and gravities confirm that at least half of the candidates are true RHB stars, with (average) parameters T eff ∼ 5000 K and log g ∼ 2.5. From the α abundances alone, the thin and thick Galactic populations are apparent in our sample. Space motions for 90% of the program stars were computed from Hipparcos and Gaia parallaxes and proper motions. Correlations between chemical compositions and Galactic kinematics clearly indicate the existence of both thin-disk and thick-disk RHB stars. © 2018. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; stars: abundances; stars: atmospheres; stars: evolution; stars: horizontal-branch

In-situ Star Formation in the Outskirts of the Large Magellanic Cloud: Gaia DR2 Confirmation. - Casetti-Dinescu, Dana I; Girard, Terrence M; Bidin, Christian Moni; Zhang, Lan; Mendez, Rene A; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F (The Astrophysical journal, 2018)
We explore the Gaia data release 2 (DR2) proper motions of six young, main-sequence stars, members of the Large Magellanic Cloud (LMC) reported by Moni Bidin et al. These stars are located in the outskirts of the disk, between 7degree and 13degree from the LMC's center where there is very low H I content. Gaia DR2 proper motions confirm that four stars formed locally, in situ, while two are consistent with being expelled via dynamical interactions from inner, more gas-rich regions of the LMC. This finding establishes that recent star formation occurred in the periphery of the LMC, where thus far only old populations were known.
Keywords: Magellanic Clouds; dept.phy; stars: early-type; stars: kinematics and dynamics

Chemical abundances in the leading arm of the Magellanic stream - Fox, Andrew J.; Barger, Kathleen A.; Wakker, Bart P.; Richter, Philipp; Antwi-Danso, Jacqueline; Casetti-Dinescu, Dana I.; Howk, J. Christopher; Lehner, Nicolas; D’Onghia, Elena; Crowther, Paul A.; Lockman, Felix J. (The Astrophysical Journal, 2018)
The Leading Arm (LA) of the Magellanic Stream is a vast debris field of H i clouds connecting the Milky Way and the Magellanic Clouds. It represents an example of active gas accretion onto the Galaxy. Previously, only one chemical abundance measurement had been made in the LA. Here we present chemical abundance measurements using Hubble Space Telescope/Cosmic Origins Spectrograph and Green Bank Telescope spectra of four AGN sightlines passing through the LA and three nearby sightlines that may trace outer fragments of the LA. We find low oxygen abundances, ranging from 4.0-2.0+2.0% solar to 12.6-4.16.0% solar, in the confirmed LA directions, with the lowest values found in the region known as LA III, farthest from the LMC. These abundances are substantially lower than the single previous measurement, S/H =35 ±7% solar, but are in agreement with those reported in the SMC filament of the trailing Stream, supporting a common origin in the SMC (not the LMC) for the majority of the LA and trailing Stream. This provides important constraints for models of the formation of the Magellanic System. Finally, two of the three nearby sightlines show high-velocity clouds with H i columns, kinematics, and oxygen abundances consistent with LA membership. This suggests that the LA is larger than traditionally thought, extending at least 20° further to the Galactic northwest. © 2018. The American Astronomical Society. All rights reserved.
Keywords: Galaxy: evolution; Galaxy: halo; ISM: abundances; Magellanic Clouds; dept.phy; quasars: absorption lines